Core values : serving Christ's cause with effectiveness and excellence - Wood, George O.; Hurst, Randy (Springfield, Mo. : Gospel Publishing House, 2007)
U. S. Assemblies of God superintendent George O. Wood shares the five core values that determine the priorities of his administration.
Passionate proclamation -- Strategic investment -- Vigorous planting -- Skillful resourcing -- Fervent prayer.
Keywords: Assemblies of God; Church growth; Evangelistic work; Wood, George O; Assemblies of God -- Management; Christian leadership; Values -- Religious aspects -- Assemblies of God